2012
DOI: 10.1248/bpb.b12-00449
|View full text |Cite
|
Sign up to set email alerts
|

Qingkailing Injection Alleviates Experimental Autoimmune Uveitis in Rats <i>via</i> Inhibiting Th1 and Th17 Effector Cells

Abstract: Qingkailing injection is a well-known composite formula of traditional Chinese medicine and is commonly used in clinical practice, which could offer immunomodulatory effect from our clinical experience on uveitis treatment by Qingkailing. We did the experiment in order to investigate the curative effect and mechanism of Qingkailing injection to rat experimental autoimmune uveitis (EAU). EAU was induced in Lewis rats by immunization IRBP1177-1191 in complete Freund's adjuvant in multi-point. We found that Qingk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…A combinatorial strategy was used where target miRNAs were predicted for the differentially expressed genes using microcosm, miRanda and miRDB Characterization of microRNA expression profiling in peripheral… enrichment and KEGG pathway analysis. Importantly, our previous study has substantiated elevated levels of IL-10 and IL-17 in EAU rats compared with normal ones [21].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…A combinatorial strategy was used where target miRNAs were predicted for the differentially expressed genes using microcosm, miRanda and miRDB Characterization of microRNA expression profiling in peripheral… enrichment and KEGG pathway analysis. Importantly, our previous study has substantiated elevated levels of IL-10 and IL-17 in EAU rats compared with normal ones [21].…”
Section: Discussionsupporting
confidence: 50%
“…For uveitis, it is involved in increased levels of inflammatory cytokines and decreased levels of regulatory cytokines, including interleukin (IL)-17 [16,17], IL-21 [18,19], IL-10 [20,21], IFN-c [22,23] and so on. Meanwhile, it has also been reported that toll-like receptors (TLRs) are closely associated with the pathogenesis of uveitis, such as TLR2 [24,25], TLR4 [24][25][26][27][28] and other TLRs [25].…”
Section: Introductionmentioning
confidence: 99%
“…Many herbal preparations have immunomodulatory effects. [47][48][49][50][51][52][53][54][55][56][57] Thus it appears reasonable to trial herbal medications in patients with IBD. On the other hand, good, large clinical trials testing the effects of herbal therapy in IBD are widely lacking.…”
Section: Herbal Treatments For Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Qingkailing (QKL) injection is widely used in the clinic for antipyretic and anti-inflammatory effects [112], but its serious adverse drug reactions have attracted attention. Caffeoylquinic acids in QKL are responsible for these adverse drug reactions.…”
Section: Quality Control Of Tcmsmentioning
confidence: 99%